2009
DOI: 10.1021/jm801654y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Small Molecule Inhibitors of a Class I Histone Deacetylase from Plasmodium falciparum

Abstract: A library of approximately 2000 small molecules biased toward inhibition of histone deacetylases was assayed for antimalarial activity in a high-throughput P. falciparum viability assay. Active compounds were cross-analyzed for induction of histone hyperacetylation in a human myeloma cell line to identify HDAC inhibitors with selectivity for P. falciparum over the human host. To verify on-target selectivity, pfHDAC-1 was expressed and purified and a biochemical assay for pfHDAC-1 activity was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 26 publications
2
94
0
Order By: Relevance
“…Several HDAC inhibitors that are potent inhibitors of asexual blood-stage P. falciparum parasites, including SAHA and TSA, have been shown to inhibit recombinant PfHDAC1 in in vitro enzyme assays (58). We and others have also demonstrated that hyperacetylation of parasite histone and nonhistone proteins and global transcriptional alterations are a functional consequence of HDAC inhibitor exposure in asexual stage parasites (31,32,58,63,69,73,75).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Several HDAC inhibitors that are potent inhibitors of asexual blood-stage P. falciparum parasites, including SAHA and TSA, have been shown to inhibit recombinant PfHDAC1 in in vitro enzyme assays (58). We and others have also demonstrated that hyperacetylation of parasite histone and nonhistone proteins and global transcriptional alterations are a functional consequence of HDAC inhibitor exposure in asexual stage parasites (31,32,58,63,69,73,75).…”
Section: Discussionmentioning
confidence: 87%
“…HDACs, enzymes involved in regulating lysine acetylation of histone and nonhistone proteins in eukaryotic cells, are a recognized drug target in asexual stage malaria parasites (30,58,69). Five HDAC-encoding genes have been identified in the P. falciparum genome (70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood-stage Plasmodium can be killed with many drugs which inhibit histone-modifying enzymes. These include the histone acetylase inhibitors curcumin and anacardic acid (23,24), the sirtuin inhibitor nicotinamide (88), and a multitude of known and novel inhibitors of type 1 and type 2 histone deacetylases (1,2,4,28,70,83). These results suggest that histone modification is crucial for normal parasite development, and deacetylase inhibitors are therefore under investigation as antimalarial drugs (3).…”
Section: What Experimental Tools Have Been Used To Study Plasmodium Ementioning
confidence: 99%
“…It would be of great interest, in order to gain further insight into the precise function of Pfcrk-3, to identify which of the several putative HDACs (one class I HDAC, two class II HDACs, and two class III sirtuins [44]) encoded by the P. falciparum genome is responsible for the activity we observed to be associated with HA-Pfcrk-3. Sensitivity to nicotinamide suggests that a class III HDAC, such as Pfsir2, is involved (45), but caution must be exercised until the enzyme is experimentally identified.…”
Section: Discussionmentioning
confidence: 99%